Suicidal ideation and psychological dating violence victimization—A short report - Gasperecz, Jackson W. S.; Baumler, Elizabeth; Wood, Leila; Temple, Jeff R. (Frontiers in Psychiatry, 2023)
As the second leading cause of death among Americans aged 10 to 34, suicide is a serious public health concern. One potential predictor of suicidality is dating violence (DV) victimization, such as any physical, psychological, or sexual abuse by a current or former intimate partner. However, little longitudinal data exists on the relationship between suicidal ideation and DV. To address this gap in knowledge, we leverage data from two years of our longitudinal study Dating It Safe. Specifically, we examine whether physical and psychological DV victimization is associated with subsequent suicidal ideation in our ethnically diverse sample of young adults (n = 678; mean age = 25 at Wave 9; 63.6% female). While physical DV victimization was not linked to suicidal ideation over time, psychological DV victimization was (χ2 = 7.28, p = 0.007 for females; χ2 = 4.87, p = 0.027 for males). That psychological abuse was potentially as or more impactful than physical violence is consistent with the broader literature on the deleterious impacts of psychological violence, as well as the limited longitudinal literature looking at DV and suicidality specifically. These findings reinforce the notion that psychological abuse is as consequential as physical violence in the long-term, has unique impacts on mental health, and points to the need for both suicide and violence intervention programs to address this form of dating violence victimization.